Faith in Allah as the Basis of Muslims’ Spiritual Intelligence - Sudi, Suriani; Sham, Fariza Md; Yama, Phayilah (International Journal of Psychosocial Rehabilitation, 2020)
Spiritual intelligence is an important aspect of one's personal development. Previously, many theories and conceptual frameworks related to spiritual intelligence were referred to Western scholars. However, the theories and conceptual frameworks presented by them are not suitable for use as a benchmark in a Muslim's life. The need for spiritual intelligence in fact has long been discussed in the Qur'anic verses and the hadiths of the prophet SAW. The theory of spiritual intelligence was also developed by Muslim scholars including al-Ghazali, Miskawaih, Ibn Sina and Najati. From that, a concept of spiritual intelligence according to Islam was formed. Understanding of the definition and concept of spiritual intelligence needs to be debunked in the Muslim community as it is a major factor in one's self-transformation and makes life more meaningful. This study outlines the basics of spiritual intelligence which is faith in Allah. The study will use content analysis methods by identifying Quranic verses and hadiths that link faith to God with spiritual intelligence and are supported by the views of Muslim scholars. The results show that faith in God is a fundamental element in determining the level of spiritual intelligence, especially for a Muslim.